2017
DOI: 10.1111/odi.12654
|View full text |Cite
|
Sign up to set email alerts
|

Salivary levels of interleukin‐8 and growth factors are modulated in patients with geographic tongue

Abstract: We consider IL-8 an inflammatory mediator, which contributes to the acute inflammatory response found in GT. EGF and VEGF also seem to be involved in the pathophysiology of GT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In our previous study, we demonstrated that patients with GT have significantly higher salivary IL‐8 output than control subjects (Dafar, Bankvall, Garsjo, et al, ). The current study demonstrates that salivary IL‐8 output was significantly increased ( p < .001) in the GT patients' group ( N = 22; mean, 1.3 ± 0.2 µg/min; median, 1 µg/min) compared with the Control group ( N = 31; mean, 0.55 ± 0.07 µg/min; median, 0.5 µg/min).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…In our previous study, we demonstrated that patients with GT have significantly higher salivary IL‐8 output than control subjects (Dafar, Bankvall, Garsjo, et al, ). The current study demonstrates that salivary IL‐8 output was significantly increased ( p < .001) in the GT patients' group ( N = 22; mean, 1.3 ± 0.2 µg/min; median, 1 µg/min) compared with the Control group ( N = 31; mean, 0.55 ± 0.07 µg/min; median, 0.5 µg/min).…”
Section: Resultsmentioning
confidence: 79%
“…In the tissue, they follow concentration gradients of chemoattractants (e.g., IL‐8, leukotriene B4, C5a, and bacterial N‐formylated peptides) toward the site of inflammation. We have recently shown that the level of the neutrophil chemoattractant IL‐8 is increased in the saliva of patients with GT (Dafar, Bankvall, Garsjo, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations